Keratitis-ichthyosis-deafness syndrome with GJB2 mutation manifesting generalized erythematous plaques of porokeratotic eccrine ostial and dermal duct nevus - Yu-Chen Chen; Julia Yu-Yun Lee; Sheau-Chiou Chao (Wolters Kluwer Medknow Publications, 2019)
Porokeratotic eccrine ostial and dermal duct nevus or porokeratotic eccrine nevus (PEN) is a rare nevoid condition characterized by asymptomatic spiny, keratotic papules, and plaques in linear distribution along Blaschko's lines on the extremities clinically and discrete vertical cornoid lamellae at eccrine ostia pathologically. Keratitis-ichthyosis-deafness (KID) syndrome manifests generalized erythematous plaques with tiny papules and keratotic spicules. Both rare diseases are associated with mutations of the GJB2 gene encoding for gap junction protein, connexin 26. We present a case of KID syndrome in an 11-year-old boy. The patient presented with bilateral hearing loss, and large erythematous plaques with grained leather-like appearance and occasional keratotic spicules on the face and trunk as well as prominent hyperkeratosis on the acral parts, especially distal digits. Skin biopsy of two skin lesions revealed features of PEN. Mutation analysis of peripheral blood revealed GJB2 c. 263C>T (p.A88V). This is the first report of GJB2 gene mutation in a Taiwanese boy with KID syndrome. The histologic features of PEN in the present case provide additional support that PEN may be part of the manifestation of KID syndrome.